Reconceptualising critical digital literacy. Issue 2 (3rd March 2016) - Pangrazio, Luciana
Abstract : While it has proved a useful concept during the past 20 years, the notion of 'critical digital literacy' requires rethinking in light of the fast-changing nature of young people's digital practices. This paper contrasts long-established notions of 'critical digital literacy' (based primarily around the critical consumption of digital forms) with the recent turn towards 'digital design literacy' (based around the production of digital forms). In doing so, three challenges emerge for the continued relevance of critical digital literacy: (1) the challenge of critiquing the ideological concerns with the digital without alienating the individual's personal affective response; (2) connecting collective concerns to do with social and educational inequalities to individual practices; and (3) cultivating a critical disposition in a context in which technical proficiency is prioritised. The paper then concludes by suggesting a model of 'critical digital design', offering a framework that might bridge the divide between critical literacy models and the more recent design-based literacy models.